2002
DOI: 10.3354/meps225029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced UV radiation on a microbenthic community during a microcosm experiment

Abstract: A microcosm experiment was conducted over a 77 d period (from 6 July to 21 September 1999) to investigate the response of a microbenthic community to the long-term reduction of ambient ultraviolet-B (UVBR, 280 to 320 nm) and ultraviolet-A (UVAR, 320 to 400 nm) radiation. Intact sediment cores were harvested from a muddy intertidal flat in the lower St. Lawrence Estuary (Quebec, Canada) and placed in an outdoor flow-through system under 3 treatments: ambient solar radiation, reduced UVBR and reduced UVR (280 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 79 publications
1
14
1
3
Order By: Relevance
“…These findings contrast with prior studies of epipelon, where EPS was occasionally less abundant in +UV treatments (Underwood et al 1999, Roux et al 2002. It is possible that periphytic EPS in our study system was relatively more resistant to UV degradation, or that any UV-induced degradation of EPS was offset by increased periphytic biomass or EPS production.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…These findings contrast with prior studies of epipelon, where EPS was occasionally less abundant in +UV treatments (Underwood et al 1999, Roux et al 2002. It is possible that periphytic EPS in our study system was relatively more resistant to UV degradation, or that any UV-induced degradation of EPS was offset by increased periphytic biomass or EPS production.…”
Section: Resultscontrasting
confidence: 56%
“…Underwood et al (1999) observed a reduction in EPS and concomitant reductions in epipelon biomass and chlorophyll a under an ambient +15% UV-B treatment. In another epipelon study, EPS was reduced in +W plots as compared to -UV plots, but only on a few sample days (Roux et al 2002). In contrast, glycan-rich EPS production increased significantly in the cyanobacterium Nostoc commune under laboratory exposures to UV-B but not UV-A (Ehling-Schulz et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…POC concentrations were determined in duplicate with a Perkin-Elmer Model 2400 CHN Analyzer from samples concentrated on pre-combusted (450°C for 5 h) Whatman GF/F filters and kept frozen (-20°C) in Petri dishes before analysis in the laboratory. In order to assess the solubilization of particulate organic material during the deployment period (Kähler & Bauerfeind 2001), dissolved organic carbon (DOC) was measured in the traps before and after deployment using a TOC-5000A Shimadzu analyzer following the procedure explained in Roux et al (2002). The export ratio (e-ratio, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…However, the benthic diatom community almost exclusively consists of pennate diatoms, producing very low, if any, amounts of UV-absorbing compounds , Roux et al 2002. Other strategies to reduce negative effects of excessive radiation including UVR are vertical migration , Waring et al 2007) and, on a community level, 'self-shading', i.e.…”
Section: Introductionmentioning
confidence: 99%